Open Surgery for Sportsman’s Hernia a Retrospective Study - Palumbo, Piergaspare; Massimi, Fanny; Lucchese, Sara; Grimaldi, Serena; Vernaccini, Nicola; Cirocchi, Roberto; Sorrenti, Salvatore; Usai, Sofia; Intini, Sergio Giuseppe (Frontiers in Surgery, 2022)
Sportsman’s hernia is a painful syndrome in the inguinal area occurring in patients who play sports at an amatorial or professional level. Pain arises during sport, and sometimes persists after activity, representing an obstacle to sport resumption. A laparoscopic/endoscopic approach is proposed by many authors for treatment of the inguinal wall defect. Aim of this study is to assess the open technique in terms of safety and effectiveness, in order to obtain the benefit of a open treatment in an outpatient management. From October 2017 to July 2019, 34 patients underwent surgery for groin pain syndrome. All cases exhibited a bulging of the inguinal posterior wall. 14 patients were treated with Lichtenstein technique with transversalis fascia plication and placement of a polypropylene mesh fixed with fibrin glue. In 20 cases, a polypropylene mesh was placed in the pre- peritoneal space. The procedure was performed in day surgery facilities. Early or late postoperative complications did not occur in both groups. All patients returned to sport, in 32 cases with complete pain relief, whereas 2 patients experienced mild residual pain. The average value of return to sport was 34.11± 8.44 days. The average value of return to play was 53.82 ± 11.69 days. With regard to postoperative pain, no substantial differences between the two techniques were detected, and good results in terms of the resumption of sport were ensured in both groups. Surgical treatment for sportsman’s hernia should be considered only after the failure of conservative treatment. The open technique is safe and allows a rapid postoperative recovery.